2000
DOI: 10.1177/000992280003900903
|View full text |Cite
|
Sign up to set email alerts
|

Risk Behaviors and the Prevalence of Chiamydia in a Juvenile Detention Facility

Abstract: The prevalence of Chlamydia trachomatis, a sexually transmitted disease, and the association of selected behavioral risk factors were assessed in a population of adolescents in two juvenile detention facilities. Urine was collected for Chlamydia testing and a brief interview conducted for risk and demographic information. Almost all of the 200 participants were sexually active, many before the age of 13 years. The prevalence of Chlamydia infection was 22.2% among female and 8.7% among male participants. Inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 14 publications
4
34
0
Order By: Relevance
“…Recent surveillance data indicated that rates of gonorrhea among adolescent detainees were 152 and 42 times greater among males and females, respectively, than among adolescents in the general population (Crosby, DiClemente, Wingood, Rose, & Levine, 2003). Low rates of condom use have also been found among adolescent offenders (Kelly, Bair, Baillargeon, & German, 2000). Many detainees have limited access to primary health care or health interventions and have lower perceived personal threat of STDs, lower personal efficacy to prevent STDs, and less favorable norms of safe sex practices (Gillmore, Morrison, Lowery, & Baker, 1994;Kelly et al, 2000).…”
Section: Sexual Risk Behaviormentioning
confidence: 99%
“…Recent surveillance data indicated that rates of gonorrhea among adolescent detainees were 152 and 42 times greater among males and females, respectively, than among adolescents in the general population (Crosby, DiClemente, Wingood, Rose, & Levine, 2003). Low rates of condom use have also been found among adolescent offenders (Kelly, Bair, Baillargeon, & German, 2000). Many detainees have limited access to primary health care or health interventions and have lower perceived personal threat of STDs, lower personal efficacy to prevent STDs, and less favorable norms of safe sex practices (Gillmore, Morrison, Lowery, & Baker, 1994;Kelly et al, 2000).…”
Section: Sexual Risk Behaviormentioning
confidence: 99%
“…For example, more than 70% have had sex before the age of 13, fewer than 25% use condoms, and chlamydia prevalence rates of 20%-30% are not uncommon (Castrucci & Martin, 2002;Kelly, Bair, Baillargeon, & German, 2000;Morris et al, 1995;Oh et al, 1998). These behaviors have been correlated with substance abuse, school truancy, and a history of childhood sexual abuse (Castrucci, Geriach, Kaufman, & Orleans, 2002;Robin et al, 2004).…”
mentioning
confidence: 99%
“…More recent studies have confirmed similar high rates of sexual activity. 9,14,15 Youth in the juvenile corrections system reported more HIV/STD risk behaviors and engaged in these behaviors at younger ages. 10 Some of these risk behaviors among juveniles were related to highly prevalent psychiatric disorders including depression, suicidal tendency, and anxiety, which predict risk behaviors such as inconsistent condom use and intravenous drug use.…”
Section: Why Screen Correctional Populations For Stds?mentioning
confidence: 99%
“…15,23 One study found that 56% of juveniles had not gone to see a health care provider within the past 12 months. 9 Another showed that, in the past year, one third of jail entrants who needed to see a provider did not do so because of cost. 24 Despite their high-risk behaviors, individuals likely to be incarcerated rarely seek care, suggesting that the correctional setting may be their first opportunity for STD testing and treatment services.…”
Section: Why Screen Correctional Populations For Stds?mentioning
confidence: 99%